Risk aversion affects economic values of blue fox breeding scheme. (19th July 2016) - Peura, J.; Kempe, R.; Strandén, I.; Rydhmer, L.
Summary: The profit and production of an average Finnish blue fox farm was simulated using a deterministic bio‐economic farm model. Risk was included using Arrow‐Prat absolute risk aversion coefficient and profit variance. Risk‐rated economic values were calculated for pregnancy rate, litter loss, litter size, pelt size, pelt quality, pelt colour clarity, feed efficiency and eye infection. With high absolute risk aversion, economic values were lower than with low absolute risk aversion. Economic values were highest for litter loss (18.16 and 26.42 EUR), litter size (13.27 and 19.40 EUR), pregnancy (11.99 and 18.39 EUR) and eye infection (12.39 and 13.81 EUR). Sensitivity analysis showed that selection pressure for improved eye health depended strongly on proportion of culled animals among infected animals and much less on the proportion of infected animals. The economic value of feed efficiency was lower than expected (6.06 and 8.03 EUR). However, it was almost the same magnitude as pelt quality (7.30 and 7.30 EUR) and higher than the economic value of pelt size (3.37 and 5.26 EUR). Risk factors should be considered in blue fox breeding scheme because they change the relative importance of traits.